Identification and molecular characterization of a novel mutation in MSH2 gene in a Lynch syndrome family. - Cudia, Bianca; Lo Monte, Attilio Ignazio; Liccardo, Raffaella; Izzo, Paola; Duraturo, Francesca (European Journal of Oncology and Environmental Health, 2018)
Background and aim of the work: The Lynch Syndrome (LS) is associated with germline mutations in one of the MisMatch Repair (MMR) genes, including MLH1, MSH2, MSH6, PMS2, MLH3 and MSH3. The molecular characterization of mutations in these MMR genes facilitates the pre-symptomatic diagnosis of subjects at risk to develop a colon cancer or a cancer LS-related. Methods: DHPLC and direct sequencing were performed for the mutation detection analysis. Results: In this study, we identified a novel frame shift mutation, the named is c.170delT in MSH2 gene that determined a premature stop codon and consequently, the formation of a truncated protein (p. Val56Glyfs*7). This is a novel mutation, as it has not been reported before in the international scientific literature. This mutation was found in two subjects (father and son) belonging to a LS family. However, they showed a different phenotype disease. Conclusion: In this study, we identified and characterized a novel MSH2 mutation; moreover, this study reaffirmed the importance of genetic testing in Lynch syndrome.